Peran Komunikasi dan Semangat Kerja terhadap Peningkatan Prestasi Kerja Pegawai Kantor Lurah Muara Dua Kota Prabumulih - Yelli Aswariningsih; Jumadi Wal’ajro; Safaruddin Safaruddin (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study was conducted at the Muara Dua Sub-District Office in Prabumulih City using a quantitative approach. The research population consisted of 28 employees, and a saturated sampling technique was employed. The variables examined were Communication (X₁), Work Enthusiasm (X₂), and Work Performance (Y). Data were analyzed using multiple linear regression through SPSS software. The results indicate that partially, communication has a significant effect on work performance (t_calculated > t_table). Similarly, work enthusiasm also shows a significant influence on employee performance. Simultaneously, both variables have a strong effect on work performance, with a coefficient of determination (R²) of [insert value, e.g., 0.65 or 65%]. This finding suggests that improving communication quality and maintaining employees’ work enthusiasm are key factors in optimizing public service performance at the sub-district administrative level.